Konstruksi Model Wakaf Perusahaan Dalam Negara Hukum Indonesia - Lukman Santoso; Miftahul Huda (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
This study aims to explore the model of management and development of company waqf assets in Malaysia and Singapore, and their relevance to the development of company waqf construction in accordance with Indonesian waqf law and the wisdom of traditions that have developed. By using an interpretive explorative type qualitative approach, this research resulted in the finding, that the construction of the management model and development of corporate waqf assets in Indonesia in accordance with the context of Indonesian waqf law and traditional wisdom are business entities, banks, universities, foundations, hospitals, cooperative. So as to realize the strengthening of the holistic corporate waqf model in Indonesia, it is necessary to strengthen the regulatory stakeholders as well as an integrative and holistic understanding among scholars.